Entrepreneurial marketing in small and medium en terprise sector: conceptual exploration - Bandara, K.B.T.U.K. (University of Jaffna, 2019)
Entrepreneurial Marketing (EM) is an essential concept for today’s small and medium enterprise (SME) sector as it enables the firms to be more entrepre neurial under limited resources conditions, and uncertain market circumstances. Although a number of definitions, theories and models have been developed for this novel concept, still there is no unifying theory or a definition in literature. Indeedthe concept of Entrepreneurial Marketing (EM) has been developed at the interface between two distinct sciences: Marketing and Entrepreneurship and it is widely accepted that EM is a best approach for the growth and survival of SMEs. Since SME’s marketing approaches are not fit with established traditional marketing theories and successful SMEs are being able to acquire a competitive advantage on their unique benefit of “smallness” and the influence of owner or operator of the business. The purpose of this paper is to get an insight of “Entrepreneurial Marketing in small and medium enterprise sector” based on recently published literature in cluding ,journal articles, conference and symposium papers, text books and rel evant websites. Accordingly, this paper brief an evolution of EM concept, an analysis of the different EM definitions, overview of the conceptual models de veloped in the prescribed area and the conceptual exploration of entrepreneurial marketing in SME sector.
Keywords: Entrepreneurial marketing; Entrepreneurship; Marketing; Small and medium enterprises